Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Using Todd-Coxeter algorithm (a handy long calculations), I could find that the subgroup $H=\langle ab,abc\rangle$ of group $$G=\langle a,b,c|abcab^{-1}=bcabc^{-1}=cabca^{-1}=1\rangle$$ is of index $1$ in $G$ and has a new presentation as $$H=\langle x,y|y^{-1}xy^2x^2=1,xy=yx^{-3}yx\rangle$$ May I ask here to have another simpler way, at least in this group. Thank you.

share|cite|improve this question
up vote 2 down vote accepted

Clearly $H=\langle ab, abc\rangle=\langle ab, c\rangle$ as $(ab^{-1})abc=c$. On the other hand, $b^{-1}=c(ab)c^{-1}$ by the first relation. Thus, $b, c\in H$. As $ab, b\in H$, $b\in H$ and so $G=\langle ab, abc\rangle=H$. We therefore have index one.

To get the presentation for $G$ in terms of $ab, abc$, we re-write the presentation we have for $G$ in terms of $ab$ and $abc$. Start by just doing this for $a$, $b$ and $c$,

$c=(ab)^{-1}(abc)=x^{-1}y$ $a=(ab)^{-1}(abc)(ab)(ab)^{-1}(abc)=x^{-1}y^2$ $b=(ab)^{-1}(abc)(ab)^{-1}(abc)^{-1}(ab)=x^{-1}yx^{-1}y^{-1}x$

Then rewriting $G$ in terms of $x$ and $y$ we get,

$H=\langle a, b, c, x, y; a=x^{-1}y^2, b=x^{-1}yx^{-1}y^{-1}x, c=x^{-1}y^2, abcab^{-1}=1, bcabc^{-1}=1, cabca^{-1}=1\rangle$

$\Rightarrow H=\langle x, y; x^{-1}y^2x^{-1}yx^{-1}y^{-1}xx^{-1}y^2x^{-1}y^2(x^{-1}yx^{-1}y^{-1}x)^{-1}=1, x^{-1}yx^{-1}y^{-1}xx^{-1}y^2x^{-1}y^2x^{-1}yx^{-1}y^{-1}x(x^{-1}y^2)^{-1}=1, x^{-1}y^2x^{-1}y^2x^{-1}yx^{-1}y^{-1}xx^{-1}y^2(x^{-1}y^2)^{-1}=1\rangle$

$\Rightarrow H=\langle x, y; x^{-1}y^2x^{-1}yx^{-1}yx^{-1}y^2x^{-1}yxy^{-1}x=1, x^{-1}yx^{-1}yx^{-1}y^2x^{-1}yx^{-1}y^{-1}xy^{-2}x=1, x^{-1}y^2x^{-1}y^2x^{-1}yx^{-1}y^{-1}x=1\rangle$

$\Rightarrow H=\langle x, y; yx^{-1}yx^{-1}yx^{-1}y^2x^{-1}yx=1, x^{-1}yx^{-1}y^2x^{-1}yx^{-1}y^{-1}xy^{-1}=1, yx^{-1}y^2x^{-1}yx^{-1}=1\rangle$

Tidy it up a bit and you should get the same as what you have (assuming that neither of us have made any mistakes in our working, which, for my part, isn't unlikely...).

share|cite|improve this answer
These calculations look tedious and thank you for it, your time specially 1729. ;) – Babak S. Oct 29 '12 at 15:50
They are as non-tedious as you are going to get! Of course, you could just use GAP... – user1729 Oct 29 '12 at 16:01
Also, I skipped lots of steps when I was doing it. For example, I didn't write the presentation $\langle a, b, c, x, y;\ldots\rangle$, I got got rid of the $a$, $b$ and $c$ without thinking about it. – user1729 Oct 29 '12 at 16:05
I see that. Thanks again for your time. I am working on your calculations to know more and find my own for another time. :) – Babak S. Oct 29 '12 at 16:18
@coffeemath: Maple can do groups?! I'm pretty sure all groups of order $p^2q$ are classified, but I cannot be sure (all groups of order $pq$ are, and this is a classic undergrad question). Also, all groups of order $p^aq^b$ are soluble (and so not simple if $ab\neq 0$). – user1729 Oct 29 '12 at 19:59

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.